2024
DOI: 10.7759/cureus.52857
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Synergistic Effects of Syzygium cumini, Moringa oleifera, and Tinospora cordifolia Against Different Candida Infections

Adedayo O Adelakun,
Ayoola Awosika,
Uzochukwu Adabanya
et al.

Abstract: Introduction The burden of multiple drug resistance in human pathogens has necessitated the search for and development of antimicrobial agents with a wide range of structural classes and potentials to selectively act on the several mechanisms of actions exhibited by the pathogens. However, most synthetic antimicrobial agents have been linked with adverse side effects and high costs, furthering the need to explore more options. Syzygium cumini , Moringa oleifera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…10 The results are aligned with reports that Syzygium species show rich medicinal applications. 13 Recent studies demonstrated the efficacy of Syzygium species against different types of bacterial strains, 14 which contain various phytochemicals that exhibit antioxidant and antimicrobial properties that result in their inhibitory abilities 15 and methanolic extracts have biological activities like antibacterial properties. 16 The findings are supported by the previous findings that Lubeg contains phenolic, [6][7] tannins, saponins, steroids, and flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…10 The results are aligned with reports that Syzygium species show rich medicinal applications. 13 Recent studies demonstrated the efficacy of Syzygium species against different types of bacterial strains, 14 which contain various phytochemicals that exhibit antioxidant and antimicrobial properties that result in their inhibitory abilities 15 and methanolic extracts have biological activities like antibacterial properties. 16 The findings are supported by the previous findings that Lubeg contains phenolic, [6][7] tannins, saponins, steroids, and flavonoids.…”
Section: Discussionmentioning
confidence: 99%